Using genomic data to develop chloroplast DNA SSRs for the Neotropical liana Stizophyllum riparium (Bignonieae, Bignoniaceae)1. (19th October 2017) - Beyer, Maila; Nazareno, Alison G.; Lohmann, Lúcia G.
Abstract : Premise of the study: We developed chloroplast microsatellite markers (cpSSRs) to be used to study the patterns of genetic structure and genetic diversity of populations of Stizophyllum riparium (Bignonieae, Bignoniaceae). Methods and Results: We used genomic data obtained through an Illumina HiSeq sequencing platform to develop a set of cpSSRs for S. riparium . A total of 36 primer pairs were developed, of which 28 displayed polymorphisms across 59 individuals from three populations. Two to 12 alleles were recorded, and the unbiased haploid diversity per locus ranged from 0.037 to 0.905. All 28 cpSSRs presented transferability to two closely related species, S. inaequilaterum and S. perforatum . Conclusions: We report a set of 28 cpSSRs for S. riparium . All markers were shown to be variable in S. riparium, indicating that these markers will be valuable for population genetic studies across S. riparium and congeneric species.